Luteotropic effects of human chorionic gonadotropin administered 7.5 days after synchronous estrous induction in Morada Nova ewes - Vergani, Gabriel Brun [UNESP]; Fonseca, Jeferson Ferreira da; Trevizan, Juliane Teramachi [UNESP]; Amaral Pereira, Veronica Schinaider do; Garcia, Alexandre Rossetto; Esteves, Sergio Novita; Brandao, Felipe Zandonadi; Goncalves Souza-Fabjan, Joanna Maria; Franco Oliveira, Maria Emilia [UNESP] (Elsevier B.V., 2020)
This study was conducted in ewes to assess effects of human chorionic gonadotropin (hCG) administration after imposing an estrous induction treatment regimen. Ewes (n = 115) were treated with a 60 mg medroxyprogesterone-intravaginal-sponge for 6 d plus 200 IU of equine chorionic gonadotmpin (eCG) im and 37.5 mu g d-cloprostenol im 36 h before sponge removal (Day 0). After natural mating, ewes having at least one corpus luteum (CL; n = 108) were administered either 1 mL of saline (G-Control; n = 53) or 300 IU of hCG (G-hCG; n = 55) on Day 7.5 after sponge removal (Day 0). Ovarian ultrasonography and blood collection were performed on Days 7.5, 13.5, 17.5, 21.5, and 30.5. Accessory CL (aCL) were observed in 81.5 % (G-hCG) and 0.0 % (G-Control) of ewes (P = 0.0001). Diameter, area, and volume of luteal tissue were greater (P < 0.05) in G-hCG from Day 13.5 to 30.5. Progesterone (P-4) concentrations were greater (P < 0.05) on Days 13.5, 17.5, 21.5 and 30.5 for ewes of the G-hCG group. Pregnancy percentage was similar (P = 0.25) between groups [47.1 % (G-control) compared with 60.0 % (G-hCG)], although total number of lambs produced by estrous synchronized ewes was greater (P = 0.005) in ewes of the G-hCG group (90.9 % compared with 66.0 %). In conclusion, hCG administration 7.5 days after sponge removal from Morada Nova ewes during the non-breeding season is an effective treatment to induce aCL formation, improve luteal tissue biometry and P4 concentrations, and to enhance the total number of lambs born.
Keywords: Accessory corpora lutea; hCG; Luteal vascularization; Luteal blood flow; Ovarian ultrasonography; Progesterone